PEMANFAATAN MEDIA DIGITAL DALAM PEMBELAJARAN DI MADRASAH IBTIDAIYAH AL-ASYHAR KARANGAGUNG PALANG TUBAN PADA ERA DIGITAL - Nur Laili Dina Hafni; Siti Mardhiyah; Mar’atus Imamah; Qoimatul, Izzah; Uut Kenanga Sari; Ika Winarti; Izzah Qoimatul Isti’adah; Fatkhul Amin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the utilization of digital media in learning at MI Al-Asyhar Palang Tuban in the digital era. The research aims to describe the implementation of digital media in the learning process, identify the obstacles faced by teachers and students, and formulate solutions to improve the effectiveness of digital-based learning. This study employed a qualitative descriptive approach conducted for one month. Data were collected through interviews and observations, while data validity was tested using source triangulation. Data analysis was carried out using the Miles and Huberman model, including data collection, data reduction, and conclusion drawing. The findings indicate that digital media such as learning videos, YouTube, podcasts, and audio learning have been implemented in several subjects and contributed positively to the learning process. The use of digital media increased students’ motivation, participation, understanding, and digital literacy skills. In addition, digital media supported the development of 21st-century skills and strengthened character and religious values through teacher guidance. However, the implementation still faced several challenges, including limited facilities, unstable internet access, and unequal teacher competence in utilizing technology. Therefore, support for infrastructure, teacher training, and collaboration between schools and parents is needed to optimize digital learning in Madrasah Ibtidaiyah.